Preparation method of supercritical foaming polylactic acid material
By adding polycaprolactone-polylactic acid copolymer and chain extender YMX-06 to polylactic acid and adopting a supercritical foaming process, the problem of pure polylactic acid being difficult to foam uniformly in supercritical CO2 fluid is solved, and a high foaming ratio and uniform cell structure are achieved, which improves the performance of the material.
Patent Information
- Application Number
- CN202411805755.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
AI Technical Summary
Pure polylactic acid is difficult to foam uniformly in supercritical CO2 fluids, resulting in low foaming ratio and uneven foam cells, which cannot meet the existing application requirements and performance requirements.
Modified polylactic acid pellets are prepared by adding polycaprolactone-polylactic acid copolymer and chain extender YMX-06, and supercritical foaming process is adopted, including three steps: saturation, foaming and decompression, to control the immersion pressure, immersion temperature, immersion time, foaming pressure and foaming temperature to achieve uniform foaming of polylactic acid.
The foaming ratio of polylactic acid is improved to reach 30-50 times, and the cell size is small, the wall is thin, the pore size is uniform, the thermal conductivity is reduced, and the material performance is excellent, meeting application needs.
Smart Images

Figure CN119613800A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of foamed polylactic acid, and in particular to a method for preparing a supercritical foamed polylactic acid material. Background Art
[0002] In the context of increasing environmental awareness, polylactic acid, as a biodegradable polymer, has become an ideal material to replace traditional non-degradable plastics because it is derived from renewable resources such as corn starch or sugarcane and can be completely degraded in the environment. However, pure polylactic acid has the disadvantages of high brittleness, low melt strength, and easy crystallization, which makes it difficult to foam. And the residue of chemical foaming agents is not conducive to safety and environmental protection. Supercritical CO2 foaming technology is a new green environmental protection technology and the trend of foaming process. It uses industrial waste gas CO2 to compress into a supercritical fluid state and penetrate into the interior of polymer materials to achieve uniform foaming. The supercritical foaming technology of polylactic acid can prepare lightweight and environmentally friendly foam materials with excellent performance. It is widely used in packaging, construction, automotive interior, medical and other fields, which helps to reduce environmental pollution and promote the development of green economy. However, pure polylactic acid is difficult to foam uniformly in supercritical CO2 fluid because of its narrow phase change temperature range, easy surface softening to block internal penetration, and easy crystallization to form crystal nuclei at supercritical temperature. Those skilled in the art urgently need to conduct in-depth research on the supercritical CO2 foaming mechanism of polylactic acid, optimize the polylactic acid formula, improve the foaming process, and increase the polylactic acid foaming ratio and uniformity to meet existing application needs and performance requirements. Summary of the invention
[0003] In view of the problems existing in the above-mentioned prior art, the present invention aims to provide a method for preparing a supercritical foamed polylactic acid material.
[0004] A method for preparing a supercritical foaming polylactic acid material comprises the following steps: first, preparing a modified polylactic acid granule material by mixing and extruding polycaprolactone-polylactic acid copolymer and chain extender YMX-06 as modifiers through an extruder, wherein the modified polylactic acid granule material has a particle size of 100 to 300 μm; second, feeding and preheating: weighing a certain amount of the modified polylactic acid granule material and feeding it into a supercritical foaming kettle; setting the preheating and heat preservation to 50° C.; third, supercritical foaming: (1) saturation stage: supercritical carbon dioxide under high pressure penetrates into the preheated modified polylactic acid particles to form a uniform swelling state, and the impregnation pressure, impregnation temperature and impregnation time are controlled; (2) foaming stage: rapidly expanding the supercritical carbon dioxide dissolved in the polymer and converting it into a gaseous state for foaming, and controlling the foaming pressure and foaming temperature; (3) decompression stage: cooling and curing at normal pressure; fourth, post-treatment: after cooling to room temperature, the material enters a mold for molding and hot pressing, and is cut after shaping to remove burrs, thereby obtaining a supercritical foaming polylactic acid material.
[0005] Furthermore, the modified polylactic acid granules in the first step are prepared by mixing 84.5% to 94.5% polylactic acid, 5% to 15% polycaprolactone-polylactic acid copolymer, and 0.5% chain extender YMX-06, and then drying at 80° C., and then extruding, drawing, and pelletizing after internal kneading in a co-rotating twin-screw extruder.
[0006] Furthermore, the extrusion pelletizing is a combination of banburying mixing and extrusion pelletizing, the extrusion temperature is: 170°C in zone 1, 180°C in zone 2, and 180°C in zone 3; the banburying time is 6 to 10 minutes, followed by extrusion, cooling, and pelletizing.
[0007] Furthermore, the foamed pellets are sieved to obtain small particles with a diameter of 100 to 300 μm and then used in the foaming stage; Furthermore, in the third step, the immersion temperature in the saturation stage is 50° C., the immersion pressure is 10 MPa, and the immersion time is 1 to 12 hours; Furthermore, in the third step, the foaming temperature of the foaming stage is 140-150° C., the foaming pressure is 20 MPa, and the time is 5-10 min.
[0008] Furthermore, the melt strength of the modified polylactic acid granules is 300-460 mN.
[0009] Further optimization of the supercritical foaming process in the CO2 supercritical state has achieved better performance.
[0010] There are two methods for CO2 supercritical foaming, namely water phase foaming and carbon dioxide gas phase foaming. The steps of the water phase foaming method are as follows: First, add 800ml of water to the foaming kettle, close the kettle cover, heat it to 90℃, pour in 20g of modified polylactic acid particles, close the kettle cover, adjust the required temperature (122-125℃), pass carbon dioxide to exhaust, then pressurize to above 7.3MPa, and hold the pressure after reaching the set temperature. After reaching the set pressure holding time, release the pressure and collect the foam particles. The steps of the carbon dioxide gas phase foaming method are as follows: First, load the modified polylactic acid particles into the mold and put them into the foaming kettle, close the kettle cover, seal it well, put it into the heating jacket, heat it to 50℃, and fill it with carbon dioxide gas to exhaust, pressurize it to above 7.3MPa for impregnation, set the temperature of the heating jacket to the foaming temperature + 100℃ after the impregnation is completed, take out the foaming kettle after reaching the foaming temperature, manually release the pressure quickly for foaming, and take out the mold and sample after cooling.
[0011] Through a series of experiments, the effects of the ratio of different modifiers to polylactic acid (PLA) matrix and foaming conditions on the final material properties were investigated, and a variety of modifiers were selected, including starch, modified epoxidized soybean oil (VESO) and bacterial cellulose nanoparticles, which can improve the crystallinity, melting temperature and compatibility of PLA with gas.
[0012] Beneficial effects of the present invention: The invention discloses a method for preparing a supercritical foaming polylactic acid material, which utilizes industrial waste gas CO2 to make it in a supercritical fluid state to penetrate into the interior of a polymer material and release pressure to achieve the purpose of foaming, thereby replacing traditional chemical solvents and chemical foaming agents and avoiding the residual foaming agent. However, pure polylactic acid is difficult to foam uniformly in a supercritical CO2 fluid due to its narrow phase change temperature range, easy surface softening to block internal penetration, and easy crystallization to form crystal nuclei at supercritical temperature, which is not conducive to foaming. The invention solves this problem by two aspects: modification and process transformation.
[0013] First, the modified polylactic acid, adding polycaprolactone-polylactic acid copolymer can improve the mobility of polylactic acid molecules and reduce the crystallization ability, solving the problems of polylactic acid particle surface softening, internal hardening, CO2 fluid cannot enter the interior, and only foaming surface; adding chain extender YMX-06 inhibits the phase separation of polycaprolactone-polylactic acid copolymer and polylactic acid matrix molecular chain through chemical cross-linking site interlocking, increasing the stability and uniformity of the system, and at the same time, the cross-linking point improves the melt strength, making the foaming hole not easy to break. Solve the shortcomings of pure polylactic acid such as low melt strength, rupture, easy crystallization, and difficult foaming.
[0014] Second, the foaming process is improved to improve the foaming ratio and uniformity of polylactic acid. The present invention conducts foaming experiments on modified polylactic acid granules of different formula systems through two supercritical foaming methods (water phase foaming and gas phase foaming), and performs physical photography comparison, density testing, expansion rate and scanning electron microscopy on the foamed samples, analyzes the relationship between raw material formula design, foaming process conditions and foaming effect, and realizes that supercritical CO2 uniformly penetrates into the polymer matrix to form tiny bubbles. Bubble collapse is not likely to occur during the bubble growth stage, the pore size distribution is uniform, the bubble size is small and the wall is thin, and the foaming effect is good. The foaming ratio of supercritical foamed polylactic acid material is significantly higher than that of pure polylactic acid, reaching 30-50 times the foaming ratio, and it is lighter and has a lower thermal conductivity (0.036W / mK, which is half of that of pure polylactic acid foaming material). BRIEF DESCRIPTION OF THE DRAWINGS
[0015] The present invention is described in detail below in conjunction with the accompanying drawings: Figure 1 Example 2 is a photo of the foamed sample; Figure 2 This is the SEM photo of the CO2 gas phase foaming sample in Example 2 (internal cell structure); Figure 3 This is the SEM photo of the CO2 gas phase foaming sample in Example 2 (surface structure); Figure 4 It is a process flow chart of the production method of the present invention. DETAILED DESCRIPTION
[0016] The present invention is described below with specific examples, but is not intended to be limiting of the present invention. Example 1
[0017] Raw materials and equipment: water phase intermittent kettle foaming kettle YJBFK130 / 12 Shanghai Yanjian Electromechanical; micro twin-screw extruder GLZS-2 Wuhan Ruiming. Electronic balance BSA124S-CW Sartorius Scientific Instruments; electric constant temperature blast drying oven DHG-9140A Shanghai Sanfa; microcomputer-controlled electronic universal testing machine UTM24059 Shenzhen Xinsansi; thermal field emission scanning electron microscope MIRA3LMHTE supercritical AN. Automatic density meter Add water to the water tank to four-fifths, put it on the shelf, and install the weighing platform. First measure the mass of the sample in the air on the platform, and press "mode" to confirm and record the mass in the air after the display is stable. Put the sample into the cage and then immerse it in water. The mass data in the water is displayed. After the display is stable, press "mode" to confirm and record the mass in the water. Then the machine automatically calculates the density value and records the experimental data. Scanning electron microscope (SEM): Glue conductive glue on the copper sheet. Powdered solid samples can be directly glued on the conductive glue. For the morphology of the cross section, first glue the bottom firmly, then connect the cross section and the copper sheet with conductive glue, and put it into the ion sputtering coating instrument for 3 minutes. Use thermal field emission scanning electron microscope to observe the microscopic morphology of the sample, the voltage is 15kV. Fuyang high amylose starch; polylactic acid 510-X-HP; chain extender YMX-06. Polycaprolactone-polylactic acid copolymer ePLA-3430A; modified epoxy soybean oil Haierma HM-01R; calcium carbonate Jiangdong Technology JD-6000Q.
[0018] (1) Preparation of modified polylactic acid granules Use a micro twin-screw extruder for internal mixing and extrusion granulation. The processing steps are as follows: First, prepare the ingredients (60g) according to the formula ratio in Table 1 and put them in an oven for drying for more than 4 hours. Turn on the micro twin-screw extruder and set the temperature (170°C in zone 1, 180°C in zone 2, and 180°C in zone 3), then put the configured materials into the hopper, and start internal mixing after all of them enter the twin screws, and count for 6 minutes. Then extrude, cool, and pelletize, collect the modified polylactic acid pellets and number them, and complete the preparation steps of the foaming raw materials. Prepare different modified polylactic acid pellet formulas as shown in Table 1: Table 1 Formula and process of different modified polylactic acid granules
[0019] Note: Formula No. 4~5 cannot be granulated due to poor ingredients and extrusion effects, and are not listed in Table 1.
[0020] (2) Water-phase supercritical CO2 bead foaming The operation steps of the water-phase foaming method are as follows: First, add 800ml of water to the foaming kettle, close the kettle cover, heat it to 90°C, pour in 20g of modified polylactic acid particles, close the kettle cover, inject carbon dioxide, pressurize to above 7.3MPa, adjust the required temperature (122-125°C), and hold the pressure after reaching the set temperature. After reaching the set holding time, release the pressure and collect the foam particles. The water-phase foaming process and the obtained foaming sample data are shown in Table 2: Table 2 Water phase foaming process and experimental data table (“-” represents too low foaming ratio) According to the expansion rate results in the table, for pure polylactic acid, the water phase foaming effect at low temperature (122-124℃) is not good. It is speculated that the lower temperature promotes the secondary crystallization of PLA, but there is not enough temperature to destroy the crystal area, resulting in dense crystal area hindering the diffusion of CO2 in the PLA matrix. Therefore, PLA needs to be modified to achieve water phase foaming at low temperature. According to the data of 10a-10i in the table, compared with pure PLA, the modified PLA particles can achieve water phase foaming at low temperature, and the maximum expansion rate of the 10i sample can reach 1780%. This is because compared with pure PLA, the softening point of modified PLA is lower. At 122-124℃, it can not only destroy the crystal area inside the material but also maintain a certain melt strength to achieve foaming without collapse. It is this characteristic that enables the modified PLA to achieve water phase foaming at low temperature.
[0021] On the other hand, for modified PLA, the analysis and comparison of data 10a-10i show the effects of temperature, pressure, holding time and discharge cooling method on the foaming expansion ratio. The results show that: (1) When the discharge cooling method is water cooling, the foaming ratio is higher than that of natural air cooling. The reason is that water cooling can achieve rapid cooling, so that the bubbles generated by the CO2 pressure relief expansion can be quickly cooled and shaped, effectively preventing the shrinkage of the bubbles. (2) Within a certain temperature range, the higher the temperature, the greater the expansion ratio. This is because high temperature increases the fluidity of the melt, resulting in more complete foaming during the pressure relief foaming process. However, if the temperature is too high, the beads will melt and stick together, and the foam will collapse, resulting in a decrease in the expansion ratio. (3) The foaming ratio of the polymer is mainly related to two factors, namely the solubility of CO2 in the PLA matrix and the fluidity of PLA. The solubility of CO2 in the PLA matrix is inversely proportional to the temperature and proportional to the pressure, but at the same time, the fluidity of PLA is proportional to the temperature and inversely proportional to the pressure. This means that simply increasing the temperature or reducing the pressure may not necessarily increase the expansion ratio of PLA. The scientific method is to increase the temperature, reduce the pressure and extend the pressure holding time, which can improve the fluidity of PLA and allow CO2 to diffuse more fully into the PLA matrix. The data 10f-10i in the table can illustrate this point. Example 2
[0022] The same modified polylactic acid granular raw material as in Example 1 was used, with a particle size of 300 μm. The equipment used was a gas-phase intermittent kettle foaming kettle SLM1000 (Beijing Century Senlang), but the water-phase supercritical CO2 bead foaming in step 1.2 was changed to gas-phase supercritical CO2 bead foaming.
[0023] (1) Gas-phase supercritical CO2 bead foaming The steps of the carbon dioxide gas phase foaming method in anhydrous system are as follows: first, the modified polylactic acid particles are loaded into the mold and placed in the foaming kettle, the kettle cover is closed and sealed, and then the heating jacket is placed, the temperature is raised to 50°C, and carbon dioxide gas is filled in for exhaust, and the pressure is increased to above 7.3MPa for impregnation. After the impregnation is completed, the heating jacket temperature is set to the foaming temperature + 100°C, and the foaming kettle is taken out after reaching the foaming temperature, and the pressure is manually quickly released for foaming. The foaming time is 5min, and the mold and sample are taken out after cooling. The process parameters of the foamed sample prepared by gas phase supercritical CO2 bead foaming are shown in Table 2.
[0024] Table 2 Gas phase supercritical CO2 bead foaming process parameters
[0025] 1. Analysis of photos of foaming samples: Place the sample on a clean table and take photos of the sample. By observing and analyzing the photos, you can see the different foaming states, such as whether there is melting adhesion on the surface, whether there are obvious large bubble ruptures, whether the volume changes are obvious, etc., and then you can judge whether the conditions are suitable for foaming. Figure 1 This is a real photo of the foamed sample.
[0026] 2. Expansion rate characterization: Use an automatic density meter to measure the density of the material before and after foaming, according to the formula: Expansion rate P = [(ρ0 / ρ1) - 1] × 100% ρ0: raw material density; ρ1: foaming density.
[0027] The density expansion rate is calculated and shown in Table 3: Table 3 Density and expansion rate data table
[0028] 3. Scanning electron microscopy (SEM): The pore structure of the foaming material was characterized using a scanning electron microscope. Figure 2 This is the SEM photo of the CO2 gas phase foaming sample (internal cell structure). Figure 3 This is the SEM photograph of the above CO2 gas phase foaming sample (surface structure).
[0029] (2) CO2 gas phase foaming expansion rate and physical image analysis See the actual photos of CO2 gas phase foaming samples for Figure 1 , place the sample on a clean table and take a picture of the actual object. By observing and analyzing the actual picture, you can see the different foaming states, such as whether there is melting adhesion on the surface, whether there are obvious large bubble ruptures, whether the volume change is obvious, etc., and then you can judge whether the conditions are suitable for foaming.
[0030] Gas phase foaming is different from water phase foaming. Since there is no water as a good suspension and dispersion medium, and gas phase foaming is carried out in the mold, the foaming ratio of gas phase foaming is lower. In addition, since the mold temperature is higher than the gas temperature in the kettle, the part of the foaming sample in contact with the mold is easy to melt, forming a denser outer layer, thereby increasing the overall density. Depending on the shape of the mold, the proportion of the dense outer layer is also different. Therefore, when discussing the expansion rate of CO2 gas phase foaming, it is necessary to combine the actual sample picture for analysis.
[0031] Gas phase foaming is analyzed by comparing Table 1. Figure 1, Table 3, where 1A~1F are pure PLA foaming under different conditions, 3A~5C are epoxidized soybean oil system foaming under different conditions, 6A-9B are copolymer system foaming under different conditions, and the detailed formula can be seen in Table 1. The following conclusions can be drawn: (1) By comparing the data, it can be seen that appropriate foaming temperature, appropriate impregnation pressure and longer impregnation time can improve the expansion rate. Too high or too low temperature will lead to poor foaming effect. Prolonging the impregnation time can slightly increase the foaming ratio, but considering the time cost of the process, the extension of the impregnation time is not considered in this design. (2) For pure PLA, a higher expansion rate can be obtained when the impregnation temperature is 50℃, the impregnation pressure is 10MPa, the impregnation time is 12h, the foaming temperature is 150℃, and the foaming pressure is 20MPa. (3) For the epoxidized soybean oil system, the temperature resistance of the material can be improved according to the increase of the modified bacterial cellulose (BC) content, so the more BC content, the higher the suitable foaming temperature. The results showed that the suitable immersion temperature for group 3 was 50℃, immersion pressure was 10MPa, immersion time was 12h, foaming temperature was 150℃, and foaming pressure was 20MPa; the suitable immersion temperature for group 4 was 50℃, immersion pressure was 8MPa, immersion time was 12h, foaming temperature was 160℃, and foaming pressure was 15MPa; the suitable immersion temperature for group 5 was 50℃, immersion pressure was 10MPa, immersion time was 12h, foaming temperature was 160℃, and foaming pressure was 22MPa. (4) For the copolymer system, the foaming performance of the formulas with different copolymer content and whether or not chain extender was added under different conditions was compared and analyzed. The results showed that the suitable immersion temperature for group 6 was 50°C, the immersion pressure was 10MPa, the immersion time was 1h, the foaming temperature was 140°C, and the foaming pressure was 20MPa; the suitable immersion temperature for group 7 was 50°C, the immersion pressure was 10MPa, the immersion time was 12h, the foaming temperature was 150°C, and the foaming pressure was 20MPa.
[0032] (3) Scanning electron microscope morphology analysis According to the analysis of the internal pore morphology, the samples with larger expansion rates have larger internal pore sizes and more uniform pores, indicating that the nucleation and diffusion of CO2 in the PLA matrix are more uniform and sufficient, and the fluidity of PLA is better during foaming, and it can be expanded by CO2 gas to form a larger pore structure.
[0033] According to the analysis of the external surface morphology, the samples with a larger expansion rate have fewer broken bubbles on the surface and show a smoother surface, which indicates that there is less gas leakage during the foaming process and the surface structure is always relatively complete, so that CO2 can more fully expand and foam the PLA matrix. However, for some samples with a smoother surface but a low foaming ratio, it means that the diffusion effect of CO2 in the PLA matrix is not good during the impregnation stage, and a good nucleation effect cannot be formed in the matrix, resulting in insufficient CO2 diffusion from the PLA matrix during foaming.
[0034] By comparing the foaming samples with different proportions and compositions, it was found that 1D, 6B, and 10i showed good comprehensive properties, including uniform pore structure, good mechanical properties, and suitable density. These results show that reasonable formula ratio and materials are crucial to obtain ideal supercritical foaming polylactic acid materials, and also provide a theoretical basis for subsequent process design.
[0035] According to the experiments and characterization analysis in the previous article, the results show that group 6B exhibits good comprehensive performance. The foaming process conditions are: immersion temperature 50℃ immersion pressure 10MPa immersion time 1h, foaming temperature 140℃, foaming pressure 20MPa. Its formula composition is: 84.5% PLA+15% copolymer+0.5% chain extender YMX-06, and its melt strength is tested to be 460mN; 7C formula composition is 94.5% PLA, 5% copolymer, 0.5% chain extender YMX-06, and its melt strength is tested to be 300mN. Example 3
[0036] Modified polylactic acid granules preparation example 2, containing 84.5% PLA + 15% copolymer + 0.5% chain extender YMX-06.
[0037] Preprocessing (1) Drying Use an oven to thoroughly dry the modified granules for 4 hours to prevent moisture from affecting the foaming process.
[0038] (2) Crushing and screening Large pieces of polylactic acid particles may affect the uniformity of foaming, so they need to be crushed into a suitable particle size range by a pulverizer. After that, the screening equipment is used to screen out particles with consistent particle size to ensure the consistency and repeatability of the foaming process. The particle size is 100 microns to facilitate the penetration and distribution of gas inside the particles.
[0039] (3) Mixing and preheating The modified polylactic acid particles are mixed evenly with the additives to ensure uniform distribution of the ingredients. Subsequently, the mixture is heated to an appropriate temperature through a preheating device to soften the material, improve fluidity during foaming, and reduce energy consumption during the foaming process.
[0040] The operation cycle of the pretreatment stage is as follows: drying for 4 hours, crushing for 20 minutes, screening for 30 minutes, mixing for 30 minutes, and preheating for 40 minutes.
[0041] Through the above pretreatment steps, it can be ensured that the polylactic acid particles have good foaming properties, laying the foundation for the subsequent supercritical foaming process.
[0042] 2. Supercritical Foaming Process The foaming stage includes three steps: saturation, foaming and decompression.
[0043] The impregnation pressure is 10MPa, the temperature is raised to 50℃, and carbon dioxide gas is filled in for exhaust, and the pressure is increased to above 7.3MPa for impregnation. The saturated impregnation lasts for 60min. The saturated stage is to expose the preheated polylactic acid particles to supercritical carbon dioxide under high pressure. Supercritical carbon dioxide can penetrate into the polymer and form a uniform dissolved state. The pressure and temperature of this stage need to be precisely controlled, and the temperature is raised for 30min to ensure that the carbon dioxide can fully combine with the polymer to prepare for the subsequent foaming process.
[0044] (2) The foaming stage is a key step. By rapidly reducing the pressure, the supercritical carbon dioxide dissolved in the polymer expands rapidly and converts into gas, forming tiny bubbles. After the impregnation is completed, the temperature of the heating jacket is set to the foaming temperature + 100°C. After reaching the foaming temperature, the foaming kettle is taken out and the pressure is manually released quickly for foaming. The foaming temperature is 140°C, the foaming pressure is 20MPa, and the foaming time is 10min.
[0045] (3) Decompression and discharging for 1 minute. After decompression, the polymer cools and solidifies under normal pressure, fixing the microstructure of the foam. In this process, rapid cooling is required to prevent bubble shrinkage, and cooling and shaping takes 9 minutes.
[0046] 3. Post-processing Cooling stage: After supercritical foaming, the material needs to be cooled quickly to fix the pore structure after foaming; Molding and hot pressing stage: After cooling to room temperature, the material enters the mold for molding and hot pressing to allow the beads to bond with each other. Cutting stage. The shaped polylactic acid foam material is cut as needed, and the burrs are removed before quality inspection. Post-processing stage operation cycle: Molding and hot pressing for 30 minutes, cutting for 30 minutes, and quality inspection for 30 minutes.
[0047] pass Figure 4 It is a process flow chart that can intuitively see the key control points in the entire production process, so as to effectively monitor and adjust in actual operation to ensure product quality and production efficiency. In addition, the flow chart is also helpful for new employee training and improving the degree of production standardization.
[0048] Note: The melt strength test was conducted using RHEOTENS71.90 at a test temperature of 180°C. The same sample was tested ten times and the average value was taken as the melt strength value of the sample.
Claims
1. A method for producing a supercritical foamed polylactic acid material, characterized in that: The method comprises the following steps:
1. Drying and extrusion pelletizing: polycaprolactone-polylactic acid copolymer and chain extender YMX-06 are used as modifiers and extruded through an extruder to prepare modified polylactic acid granules with a particle size of 100 to 300 μm; 2. Feeding and preheating: a certain amount of modified polylactic acid granules are weighed and put into a supercritical foaming kettle; the preheating and heat preservation is set to 50° C.
3. Supercritical foaming: (1) Saturation stage: supercritical carbon dioxide under high pressure penetrates into the preheated modified polylactic acid particles to form a uniform swelling state, and the impregnation pressure, impregnation temperature and impregnation time are controlled; (2) Foaming stage: supercritical carbon dioxide dissolved in the polymer is rapidly expanded and converted into a gaseous state for foaming, and the foaming pressure and foaming temperature are controlled; (3) Decompression stage: cooling and solidification under normal pressure; 4. Post-treatment: after cooling to room temperature, the material enters a mold for molding and hot pressing, and is cut after shaping to remove burrs, thereby obtaining a supercritical foamed polylactic acid material.
2. The method for preparing the supercritical foamed polylactic acid material according to claim 1, characterized in that: The modified polylactic acid granules in the first step are 84.5% to 94.5% polylactic acid, 5% to 15% polycaprolactone-polylactic acid copolymer, and 0.5% chain extender YMX-06. The mixture is dried at 80°C, kneaded in a co-rotating twin-screw extruder, extruded, stretched, and pelletized.
3. The method for preparing the supercritical foamed polylactic acid material according to claim 1, characterized in that: The extrusion pelletizing is a process of internal mixing and extrusion pelletizing. The extrusion temperatures are: 170° C. in the first zone, 180° C. in the second zone, and 180° C. in the third zone. The internal mixing time is 6 to 10 minutes, followed by extrusion, cooling, and pelletizing.
4. The method for preparing the supercritical foamed polylactic acid material according to claim 1, characterized in that: In the first step, the pelletized material is screened to obtain small particles with a diameter of 100 to 300 μm.
5. The method for preparing the supercritical foamed polylactic acid material according to claim 1, characterized in that: In the saturation stage of the third step, the immersion temperature is 50° C., the immersion pressure is 10 MPa, and the immersion time is 1 to 12 hours.
6. The method for preparing the supercritical foamed polylactic acid material according to claim 1, characterized in that: The foaming temperature of the foaming stage in the third step is 140-150° C., the foaming pressure is 20 MPa, and the time is 5-10 minutes.
7. The method for preparing a supercritical foamed polylactic acid material according to claim 1, characterized in that: The melt strength of the modified polylactic acid granules is 300-460 mN.
8. A supercritical foamed polylactic acid material obtained by the preparation method according to any one of claims 1 to 7.
Citation Information
Cited By
Temperature driving-piezoresistive sensor and preparation method thereof
CN120535812A
Low-density high-strength low-carbon foam concrete and preparation method thereof
CN120664842A